Analysis of value-added and operational development strategy for IKM Rumah Kompos Masaro (TPS 3R Bulila) in Telaga District, Gorontalo Regency. - Kairupan, Daning Nurhalisa; Gunawan, Wawan; Sofiatin, Sofiatin (Journal of Management and Digital Business, 2024)
Talumelito Gorontalo landfill capacity is 75% filled. The only TPS 3R that processes organic waste in Gorontalo Regency is TPS 3R Bulila or IKM Rumah Kompos Masaro. IKM Rumah Kompos Masaro collaborates with PT. Masaro produces solid organic fertilizer from the leaves and twigs of the Bulila community. This research aims to calculate added value and analyze strategies for developing operational waste management at the IKM Rumah Kompos Masaro. This research uses qualitative-quantitative descriptive methods, such as direct observation techniques, interviews, and distributing questionnaires. Sampling was carried out using the purposive sampling method. Based on the analysis of added value calculations using the modified Hayami method, it is known that the compost product produced by IKM Rumah Kompos Masaro has an added value of IDR. 563.1 per kg of compost, with a ratio of 47%, which is relatively high. Twelve development strategies that can be implemented to optimize the operations of Rumah Kompos Masaro IKM were formulated using the SWOT method. The highest priority strategy based on the QSPM method analysis is strategy one: carry out innovative outreach regarding waste management so that it can attract public interest and participation.